Caffeoylquinic acids induce cell death and cell cycle arrest on HCT 116 cells via formation of extracellular H2O2and quinones - Teoh, Wuen Yew; Wahab, Norhanom Abdul; Sim, Kae Shin (Faculty of Science, Chiang Mai University, 2018)
Caffeoylquinic acids are frequently present in variety of medicinal plants, fruits, vegetables and beverages. These phenolic acids are widely accepted as antioxidants but have pro-oxidant activity under certain condition. The cell death and cell cycle arrest on HCT 116 human colon carcinoma cells were observed by flow cytometry when treated with 5-O-caffeoylquinic acid (CQ) and 3,5-dicaffeoylquinic acid (DCQ) at 1 and 2 mg/ml. The addition of cell impermeable catalase and reduced glutathione (GSH) could protect HCT 116 cells from cell death and cell cycle arrest effect of CQ and DCQ. It was observed that CQ and DCQ generated extracellular hydrogen peroxide (H2O2) and quinones in the culture medium. These in vitro data showed that caffeoylquinic acids have to undergo oxidative mechanism in order to induce anti-proliferation effect on colon cancer cells and this may be beneficial in prevention or treatment of colorectal cancer.